The Influence Of Liquidity On Financial Performance On PT. Garuda Indonesia Tbk. Period 2020-2022 - Dina Aprilia; M. Oktaviannur (International Journal of Economics, Business and Innovation Research, 2024)
This study assesses the impact of liquidity ratios on the financial performance of PT Garuda Indonesia Tbk. from 2020 to 2022. Multiple linear regression analysis was performed on financial statement data to determine the association between current ratio (CR), quick ratio (QR), and cash ratio (Cash) with return on asset (ROA). The findings revealed that CR and QR have a considerable favorable influence on ROA, however the Cashratio had no significant impact. The implication is that firm management should consider CR and QR when optimizing financial performance.This research does not use sample methodologies because it is a case study of a single organization. This analysis utilizes financial statement data from PT Garuda Indonesia Tbk. from 2020 to 2022, obtained from the Indonesia Stock Exchange's official website. SPSS version 29 was used to do multiple linear regression analysis. The study's findings revealed that CR and QR have a substantial impact on financial success, however the Cash ratio does not.